Tire adhesion inhibitor, pavement asphalt emulsion composition, method for producing the same, and pavement

A copolymer with specific structural units is added to asphalt emulsions to address thermal stability and stickiness issues, enhancing storage stability and reducing tire adhesion, thus improving pavement performance.

JP2025008536AActive Publication Date: 2025-01-20TOA ROAD CORPORATION +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023110777
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Asphalt emulsions used in pavement applications suffer from poor thermal stability and high stickiness, leading to tire adhesion issues and surface staining, particularly at high temperatures.

Method used

Incorporation of a copolymer with specific structural units derived from monomers represented by general formulas (1) and (2) and hydroxyalkyl (meth)acrylate into asphalt emulsions to enhance storage stability and reduce stickiness.

Benefits of technology

The copolymer-enhanced asphalt emulsions exhibit improved storage stability at high temperatures and form a less sticky film, reducing tire adhesion and surface staining, while maintaining effective adhesion properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008536000018
    Figure 2025008536000018
  • Figure 2025008536000001
    Figure 2025008536000001
  • Figure 2025008536000002
    Figure 2025008536000002
Patent Text Reader

Abstract

To provide a tire adhesion inhibitor used in a pavement asphalt emulsion composition, a pavement asphalt emulsion composition, a method for producing the same, and a pavement, where the pavement asphalt emulsion composition exhibits excellent storage stability at high temperatures and forms an asphalt coating with reduced stickiness.SOLUTION: A tire adhesion inhibitor contains a copolymer comprising: a structural unit (a) derived from a monomer represented by general formula (1); a structural unit (b) derived from a monomer represented by general formula (2); and a structural unit (c) derived from a hydroxyalkyl (meth)acrylate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tire adhesion inhibitor, an asphalt emulsion composition for paving and a method for producing the same, and a pavement. [Background technology]

[0002] Asphalt is generally used in a liquid form by heating, but it is known that asphalt is sometimes emulsified in water so that it can be used at room temperature without heating. Such an emulsion is called asphalt emulsion. Asphalt emulsions are used in pavement surface treatment, stabilization, tack coats, prime coats, etc. Tack coats are used to improve the adhesion of a newly paved asphalt mixture layer to the asphalt mixture layer below, as well as to joints and structures. Prime coats are applied on top of the upper subgrade to stabilize the subgrade and improve the compatibility of the subgrade with the asphalt mixture layer above it.

[0003] The asphalt emulsion used for the tack coat is "PK-4" as specified in the Japanese Industrial Standard JIS K 2208 (2000), and the asphalt emulsion used for the prime coat is "PK-3" as specified in the same standard. Asphalt coatings formed using these asphalt emulsions are sticky, especially in the summer when the road surface temperature is high, asphalt may adhere to the tires of construction machines, causing the coating on the construction surface to peel off, or the asphalt that adheres to the tires may stain the road surface outside the construction site.

[0004] For example, Patent Document 1 discloses an asphalt emulsion composition containing specific amounts of an asphalt emulsion and colloidal silica, and it is said that an asphalt coating film formed using the asphalt emulsion composition can reduce stickiness. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-91761 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the asphalt emulsion composition described in Patent Document 1 has poor thermal stability and is not considered to have sufficient storage stability at high temperatures (60° C. or higher). In addition, although the asphalt coating film formed using the asphalt emulsion composition can suppress stickiness, there is still room for further improvement.

[0007] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a tire adhesion inhibitor for use in an asphalt emulsion composition for paving, which is capable of forming an asphalt coating having excellent storage stability at high temperatures and reduced stickiness, an asphalt emulsion composition for paving and a method for producing the same, and a pavement. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by using a tire adhesion inhibitor containing a copolymer having a specific structure. The present invention was completed based on this finding. That is, the present invention is as follows.

[0009] [1] A tire adhesion inhibitor characterized by containing a copolymer including a structural unit (a) derived from a monomer represented by the following general formula (1), a structural unit (b) derived from a monomer represented by the following general formula (2), and a structural unit (c) derived from a hydroxyalkyl (meth)acrylate:

[0010] [ka] [In the formula, R 1represents an alkenyl group having 2 to 5 carbon atoms; A 1 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n1 represents the average number of moles of the oxyalkylene group added, and is a number from 1 to 100. R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.]

[0011] [ka] [In the formula, R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; m represents a number from 0 to 2. 2 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n2 represents the average number of moles of the oxyalkylene group added and is a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.] [2] The tire adhesion inhibitor according to the above [1], wherein the copolymer has a content of the structural unit (a) of 5 to 30 mass %, a content of the structural unit (b) of 15 to 60 mass %, and a content of the structural unit (c) of 30 to 80 mass %. [3] The tire adhesion inhibitor according to the above [1] or [2], wherein the hydroxyalkyl (meth)acrylate is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate. [4] The adhesion inhibitor to a tire according to any one of the above [1] to [3], wherein the copolymer has a weight average molecular weight (Mw) of 5,000 to 100,000. [5] A copolymer including a structural unit (a) derived from a monomer represented by the following general formula (1), a structural unit (b) derived from a monomer represented by the following general formula (2), and a structural unit (c) derived from a hydroxyalkyl (meth)acrylate, and an asphalt emulsion including asphalt, an emulsifier, and water, The asphalt emulsion composition for paving, wherein the asphalt emulsion is at least one type of asphalt emulsion selected from the group consisting of cationic, anionic and nonionic asphalt emulsions.

[0012] [ka] [In the formula, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n1 represents the average number of moles of the oxyalkylene group added, and is a number from 1 to 100. R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.]

[0013] [ka] [In the formula, R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; m represents a number from 0 to 2. 2 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n2 represents the average number of moles of the oxyalkylene group added and is a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.] [6] The asphalt emulsion composition for paving described in [5] above, wherein the content of the copolymer is 0.2 to 25 parts by mass per 100 parts by mass of the asphalt emulsion. [7] The asphalt paving emulsion composition according to the above [5] or [6], wherein the hydroxyalkyl (meth)acrylate is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate. [8] A method for producing the asphalt emulsion composition for paving according to any one of [5] to [7] above, A method for producing an asphalt emulsion composition for paving, comprising the following step (i) or step (ii): Step (i): A step of mixing the copolymer with an emulsion containing the emulsifier and the water, and adding the asphalt to the resulting mixture to emulsify it. Step (ii): A step of emulsifying the asphalt with an emulsion containing the emulsifier and the water, and mixing the copolymer into the resulting asphalt emulsion. [9] A method for producing the asphalt emulsion composition for paving described in [8] above, comprising the step (ii).

[10] A pavement having one or more base layers and a surface layer in this order on a roadbed, and an asphalt emulsion layer at least between the roadbed and the base layer and between the base layer and the surface layer, A pavement, wherein the asphalt emulsion layer is formed using the asphalt emulsion composition for paving described in any one of [5] to [7] above. Effect of the Invention

[0014] According to the present invention, it is possible to provide a tire adhesion inhibitor for use in an asphalt emulsion composition for paving, which is capable of forming an asphalt coating having excellent storage stability at high temperatures and reduced stickiness, an asphalt emulsion composition for paving and a method for producing the same, and a pavement. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a schematic diagram showing one form of a cross section of a pavement according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In this specification, the lower limit and upper limit described in stages for the preferred numerical range (e.g., the range of the content, etc.) can be independently combined. For example, from the description of the lower limit of "preferably 10 or more, more preferably 30 or more, and even more preferably 40 or more" and the description of the upper limit of "preferably 90 or less, more preferably 80 or less, and even more preferably 70 or less", it is also possible to select a range combining the lower limit and upper limit independently selected, such as "10 or more and 70 or less", "30 or more and 70 or less", and "40 or more and 80 or less". In addition, from the same description, it is also possible to select a range simply specifying either the lower limit or the upper limit, such as "40 or more" or "70 or less". In the present specification, in the description of a numerical range, for example, "10 to 90" is synonymous with "10 or more and 90 or less." In the description of a numerical range, the numerical values ​​of "greater than or equal to," "less than or equal to," "less than," and "greater than" can also be arbitrarily combined.

[0017] [Tire adhesion inhibitor] The tire adhesion inhibitor of the present embodiment contains a copolymer including a structural unit (a) derived from a monomer represented by the following general formula (1), a structural unit (b) derived from a monomer represented by the following general formula (2), and a structural unit (c) derived from a hydroxyalkyl (meth)acrylate.

[0018] [ka]

[0019] [In the formula, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n1 represents the average number of moles of the oxyalkylene group added, and is a number from 1 to 100. R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.]

[0020] [ka]

[0021] [In the formula, R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; m represents a number from 0 to 2. 2 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n2 represents the average number of moles of the oxyalkylene group added and is a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.]

[0022] The tire adhesion inhibitor of the present embodiment contains the copolymer, and thus it is possible to obtain an asphalt emulsion composition for paving that is capable of forming an asphalt coating having excellent storage stability at high temperatures and reduced stickiness. In the copolymer, the structural unit (a) derived from the monomer represented by the general formula (1) and the structural unit (c) derived from the hydroxyalkyl (meth)acrylate have the property of being easily compatible with water, while the structural unit (b) derived from the monomer represented by the general formula (2) has the property of being less compatible with water. Therefore, when an asphalt emulsion composition containing the copolymer is sprayed or applied to asphalt, the water-compatible portion of the copolymer is oriented on the asphalt surface during the process of water evaporation in the composition, and it is presumed that the resulting asphalt coating has reduced stickiness and is less likely to adhere to tires, etc.

[0023] (Monomer represented by general formula (1)) The monomer constituting the structural unit (a) contained in the copolymer is represented by the following general formula (1).

[0024] [ka]

[0025] In the general formula (1), R 1represents an alkenyl group having 2 to 5 carbon atoms; A 1 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O, they may be the same or different. n1 represents the average number of moles of the oxyalkylene group added, and is a number from 1 to 100. R 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.

[0026] R 1 R is preferably an alkenyl group having 3 to 5 carbon atoms. 1 Specific examples of include an allyl group, a methallyl group, a residue of 3-methyl-3-buten-1-ol, etc. Among these, an allyl group is preferable.

[0027] The above A 1 O is preferably an oxyalkylene group having 2 to 12 carbon atoms, more preferably an oxyalkylene group having 2 to 6 carbon atoms, and even more preferably an oxyalkylene group having 2 to 4 carbon atoms. Examples of the oxyalkylene group include an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit). Among these, from the viewpoint of further exerting the effects of the present invention, an oxyethylene group and an oxypropylene group are preferred, and an oxyethylene group is more preferred.

[0028] The above A 1 When there are multiple O's, they may be the same or different. 1 In the case where a plurality of O's are contained, for example, there may be mentioned an embodiment in which two or more kinds of oxyalkylene groups selected from the group consisting of an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit) are mixed, and there may be an embodiment in which an oxyethylene group and an oxypropylene group are mixed, or there may be an embodiment in which an oxyethylene group and an oxybutylene group are mixed. 1 In an embodiment containing a plurality of O, the addition of two or more types of oxyalkylene groups may be in a block form or a random form.

[0029] The n1 is the average number of moles of oxyalkylene groups added. In this specification, the average number of moles added means the average number of moles of alkylene glycol units added to 1 mole of monomer. The lower limit of n1 is usually 1 or more, 2 or more, 3 or more, preferably 4 or more, 5 or more, 6 or more, more preferably 7 or more, 8 or more, 9 or more, and even more preferably 10 or more. The upper limit is usually 100 or less, preferably 90 or less, 80 or less, 60 or less, 50 or less, and more preferably 40 or less. Therefore, n1 is usually 1 to 100, 2 to 100, 3 to 100, 4 to 100, 5 to 100, preferably 6 to 90, 7 to 80, 8 to 60, 9 to 50, and more preferably 10 to 40. When n1 is within the above range, the storage stability at high temperatures of the asphalt emulsion composition containing the copolymer is more excellent, and the stickiness of the obtained asphalt coating can be further reduced.

[0030] R 2 is a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms, preferably a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms, and even more preferably a hydrogen atom or a methyl group. The hydrocarbon group may be either saturated or unsaturated, and may be linear, branched, or cyclic. Of these, a saturated hydrocarbon group is preferred, and a linear saturated hydrocarbon group is more preferred.

[0031] Examples of the monomer represented by the general formula (1) include (poly)ethylene glycol (meth)allyl ether, (poly)ethylene glycol 3-methyl-3-butenyl ether, (poly)ethylene glycol (poly)propylene glycol (meth)allyl ether, (poly)ethylene (poly)propylene glycol (meth)allyl ether, (poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether, (poly)ethylene (poly)butylene glycol (meth)allyl ether, and (poly)ethylene (poly)butylene glycol. Examples of the alkoxy group include 3-methyl-3-butenyl ether, methoxy(poly)ethylene glycol (meth)allyl ether, methoxy(poly)ethylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene (poly)propylene glycol (meth)allyl ether, methoxy(poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether, methoxy(poly)ethylene (poly)butylene glycol (meth)allyl ether, and methoxy(poly)ethylene (poly)butylene glycol 3-methyl-3-butenyl ether. Among these, from the viewpoint of the balance between hydrophilicity and hydrophobicity, (poly)ethylene glycol (meth)allyl ether, (poly)ethylene glycol (poly)propylene glycol (meth)allyl ether, (poly)ethylene (poly)propylene glycol (meth)allyl ether, (poly)ethylene glycol 3-methyl-3-butenyl ether, and (poly)ethylene (poly)propylene glycol 3-methyl-3-butenyl ether are preferred, and (poly)ethylene glycol (meth)allyl ether is more preferred. The monomer represented by the general formula (1) may be used alone or in combination of two or more kinds.

[0032] In this specification, "(meth)allyl" means both allyl and methallyl. Furthermore, "(meth)acrylate" means both acrylate and methacrylate. "(Poly)" means that one or more of the constituent element or raw material described immediately after it is bonded.

[0033] Examples of the method for producing the monomer represented by the general formula (1) include, but are not limited to, a method of adding an alkylene oxide to an unsaturated alcohol such as allyl alcohol, methallyl alcohol, or 3-methyl-3-buten-1-ol.

[0034] (Monomer represented by general formula (2)) The monomer constituting the structural unit (b) contained in the copolymer is represented by the following general formula (2).

[0035] [ka]

[0036] In the general formula (2), R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; m represents a number from 0 to 2. 2 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are multiple O, they may be the same or different. n2 is the average number of moles of the oxyalkylene group added and represents a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.

[0037] R 3 , R 4 and R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, and an isopropyl group. Among these, a methyl group and an ethyl group are preferred, and a methyl group is more preferred.

[0038] The above A 2O is preferably an oxyalkylene group having 2 to 12 carbon atoms, more preferably an oxyalkylene group having 2 to 6 carbon atoms, and even more preferably an oxyalkylene group having 2 to 4 carbon atoms. Examples of the oxyalkylene group include an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit). Among these, from the viewpoint of further exerting the effects of the present invention, an oxyethylene group and an oxypropylene group are preferred, and an oxyethylene group is more preferred.

[0039] The above A 2 When there are multiple O's, they may be the same or different. 2 In the case where a plurality of O's are contained, for example, there may be mentioned an embodiment in which two or more kinds of oxyalkylene groups selected from the group consisting of an oxyethylene group (ethylene glycol unit), an oxypropylene group (propylene glycol unit), and an oxybutylene group (butylene glycol unit) are mixed, and there may be an embodiment in which an oxyethylene group and an oxypropylene group are mixed, or there may be an embodiment in which an oxyethylene group and an oxybutylene group are mixed. 2 In an embodiment containing a plurality of O, the addition of two or more types of oxyalkylene groups may be in a block form or a random form.

[0040] The above m represents a number of 0 to 2, and is preferably 0 or 1.

[0041] The n2 is the average number of moles of oxyalkylene groups added. The lower limit of n2 is usually 1 or more, 2 or more, 3 or more, preferably 4 or more, 5 or more, 6 or more, more preferably 7 or more, 8 or more, 9 or more, and even more preferably 10 or more. The upper limit is usually 100 or less, preferably 90 or less, 80 or less, 60 or less, 50 or less, and more preferably 40 or less. Therefore, n2 is usually 1 to 100, 2 to 100, 3 to 100, 4 to 100, 5 to 100, preferably 6 to 90, 7 to 80, 8 to 60, 9 to 50, and more preferably 10 to 40. When n2 is within the above range, the storage stability at high temperatures of the asphalt emulsion composition containing the copolymer is more excellent, and the stickiness of the obtained asphalt coating can be further reduced.

[0042] The X is a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms, and from the viewpoint of further exerting the effects of the present invention, is preferably a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrogen atom or a hydrocarbon group having 1 to 5 carbon atoms, and even more preferably a hydrogen atom or a methyl group. The hydrocarbon group may be either saturated or unsaturated, and may be any of linear, branched, and cyclic. Among them, a saturated hydrocarbon group is preferred, and a linear saturated hydrocarbon group is more preferred.

[0043] Examples of the monomer represented by the general formula (2) include (poly)alkylene glycol (meth)acrylates such as (poly)ethylene glycol (meth)acrylate, (poly)ethylene (poly)propylene glycol (meth)acrylate, and (poly)ethylene (poly)butylene glycol (meth)acrylate; and methoxy(poly)alkylene glycol (meth)acrylates such as methoxy(poly)ethylene glycol (meth)acrylate, methoxy(poly)ethylene (poly)propylene glycol (meth)acrylate, and methoxy(poly)ethylene (poly)butylene glycol (meth)acrylate. Among these, from the viewpoint of the balance between hydrophilicity and hydrophobicity, (poly)alkylene glycol (meth)acrylate and methoxy(poly)ethylene glycol (meth)acrylate are preferred, and methoxy(poly)ethylene glycol (meth)acrylate is more preferred. The monomer represented by the general formula (2) may be used alone or in combination of two or more kinds.

[0044] The method for producing the monomer represented by the general formula (2) includes, for example, a method of esterifying a (poly)alkylene glycol with an unsaturated monocarboxylic acid. An example of the unsaturated carboxylic acid includes, for example, (meth)acrylic acid. An example of the (poly)alkylene glycol includes, for example, (poly)ethylene glycol, (poly)ethylene (poly)propylene glycol, (poly)ethylene (poly)butylene glycol, methoxy(poly)ethylene glycol, methoxy(poly)ethylene (poly)propylene glycol, and methoxy(poly)ethylene (poly)butylene glycol.

[0045] (Hydroxyalkyl (meth)acrylate) The hydroxyalkyl (meth)acrylate constituting the structural unit (c) contained in the copolymer is a compound having a (meth)acryloyloxy group and an alkyl group substituted with a hydroxy group. The number of carbon atoms in the alkyl group in the hydroxyalkyl (meth)acrylate is preferably 1 to 6, more preferably 1 to 4. The alkyl group may be linear or branched, and may be, for example, a linear alkyl group having 1 to 4 carbon atoms.

[0046] Examples of the hydroxyalkyl (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate. Among them, from the viewpoint of the balance between hydrophilicity and hydrophobicity, at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate is preferred, at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate is more preferred, and at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate is even more preferred. The hydroxyalkyl (meth)acrylates may be used alone or in combination of two or more.

[0047] (Other monomers) The copolymer may further contain a structural unit (d) derived from a monomer represented by the general formula (1), a monomer represented by the general formula (2), and a monomer copolymerizable with the hydroxyalkyl (meth)acrylate. An example of the monomer that constitutes the structural unit (d) is a monomer represented by the following general formula (3).

[0048] [ka]

[0049] In general formula (3), R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or -(CH2) r COOM 2 Represents M 1 and M 2 Each of the groups independently represents a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group. r is an integer of 0 to 2. Here, -(CH2) r COOM 2 -COOM 1 or other -(CH2) r COOM 2 When an anhydride is formed with M 1 and M 2 does not exist.

[0050] R 6 , R 7 and R 8 Examples of the alkyl group having 1 to 3 carbon atoms as the alkyl group include a methyl group, an ethyl group, an n-propyl group, and an isopropyl group. Among these, a methyl group and an ethyl group are preferred, and a methyl group is more preferred.

[0051] Said M 1 and M 2 are each independently a hydrogen atom, an alkali metal, an alkaline earth metal, an ammonium group, an alkylammonium group, or a substituted alkylammonium group. Among these, from the viewpoint of further exerting the effects of the present invention, a hydrogen atom, an alkali metal, or an alkaline earth metal is preferred, and a hydrogen atom is more preferred.

[0052] The above r is an integer of 0 to 2, preferably 0 or 1, and more preferably 0.

[0053] Examples of the monomer represented by the general formula (3) include unsaturated monocarboxylic acid monomers and unsaturated dicarboxylic acid monomers. Examples of the unsaturated monocarboxylic acid monomers include acrylic acid, methacrylic acid, and crotonic acid, as well as their salts (e.g., monovalent metal salts, ammonium salts, and organic amine salts). Examples of the unsaturated dicarboxylic acid monomers include maleic acid, itaconic acid, citraconic acid, and fumaric acid, as well as their salts (e.g., monovalent metal salts, ammonium salts, and organic amine salts), and their anhydrides. From the viewpoint of further exerting the effects of the present invention, the monomer represented by the general formula (3) is preferably acrylic acid, methacrylic acid, maleic acid, and their salts, and more preferably acrylic acid, methacrylic acid, and their salts. The monomer represented by the general formula (3) may be used alone or in combination of two or more kinds.

[0054] When the copolymer contains the structural unit (d), it may be a salt of the copolymer. Examples of the salt of the copolymer include monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts of the copolymer.

[0055] (Ratio of constituent units) When all the structural units contained in the copolymer or a salt thereof are taken as 100 mass %, the mass ratio of each structural unit is, for example, as follows. The mass ratios below usually correspond to the amounts of monomers blended when the copolymer or a salt thereof is produced.

[0056] The content of the structural unit (a) derived from the monomer represented by the general formula (1) contained in the copolymer is preferably 5 to 30 mass%, more preferably 6 to 25 mass%, and even more preferably 8 to 20 mass%. When the content of the structural unit (a) is 5 mass% or more, the stickiness of the obtained asphalt coating can be further reduced, and when it is 30 mass% or less, the storage stability at high temperatures of the asphalt emulsion composition containing the copolymer is more excellent.

[0057] The content of the structural unit (b) derived from the monomer represented by the general formula (2) contained in the copolymer is preferably 15 to 60 mass%, more preferably 20 to 55 mass%, and even more preferably 25 to 50 mass%. When the content of the structural unit (b) is 15 mass% or more, the high temperature storage stability of the asphalt emulsion composition containing the copolymer is superior, and when it is 60 mass% or less, the stickiness of the obtained asphalt coating can be further reduced.

[0058] The content of the structural unit (c) derived from the hydroxyalkyl (meth)acrylate contained in the copolymer is preferably 30 to 80 mass%, more preferably 35 to 70 mass%, and even more preferably 40 to 60 mass%. When the content of the structural unit (c) is 30 mass% or more, the stickiness of the obtained asphalt coating can be further reduced, and when it is 80 mass% or less, the storage stability at high temperatures of the asphalt emulsion composition containing the copolymer is more excellent.

[0059] When the copolymer contains the structural unit (d), its content is preferably 1 to 10 mass%, more preferably 2 to 8 mass%, and even more preferably 3 to 8 mass%. When the content of the structural unit (d) is 1 mass% or more, the stickiness of the obtained asphalt coating can be further reduced, and when it is 10 mass% or less, the storage stability at high temperatures of the asphalt emulsion composition containing the copolymer is more excellent.

[0060] (Physical properties of copolymer) The weight average molecular weight (Mw) of the copolymer is preferably 5,000 to 100,000, more preferably 6,000 to 95,000, even more preferably 8,000 to 90,000, even more preferably 10,000 to 80,000, and even more preferably 10,000 to 50,000. When the Mw is 5,000 or more, aggregation of the copolymer can be suppressed, and the high temperature storage stability of the asphalt emulsion composition containing the copolymer is more excellent. Also, when the Mw is 100,000 or less, the asphalt emulsion can be used without affecting its stability. The weight average molecular weight (Mw) of the copolymer is a molecular weight in terms of polyethylene glycol, measured by gel permeation chromatography (GPC) according to the method described in the Examples, using a calibration curve prepared using standard polyethylene glycol samples with known molecular weights.

[0061] The molecular weight distribution (Mw / Mn) of the copolymer is preferably 1.01 to 10.0, more preferably 1.3 to 9.0, even more preferably 1.5 to 8.0, still more preferably 1.8 to 6.0, and even more preferably 2.0 to 4.0. When Mw / Mn is within the above range, the asphalt emulsion composition containing the copolymer has excellent storage stability at high temperatures, and an asphalt coating film with reduced stickiness can be obtained. The molecular weight distribution (Mw / Mn) of the copolymer means the ratio of weight average molecular weight (Mw) / number average molecular weight (Mn) calculated as standard polyethylene glycol, determined by GPC measurement.

[0062] (Method of Producing Copolymer) The copolymer can be produced by copolymerizing the monomers from which the respective structural units are derived by a known method, such as polymerization in a solvent or bulk polymerization.

[0063] Examples of the solvent used in the polymerization in a solvent include water, lower alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., alicyclic or aliphatic hydrocarbons such as cyclohexane, n-hexane, etc., esters such as ethyl acetate, etc., ketones such as acetone, methyl ethyl ketone, etc. From the viewpoint of the solubility of the raw material monomers and the resulting copolymer, it is preferable to use one or more selected from the group consisting of water and lower alcohols, and among them, it is more preferable to use water.

[0064] When copolymerization is carried out in a solvent, each monomer and the polymerization initiator may be continuously dropped into a reaction vessel, or a mixture of each monomer and the polymerization initiator may be continuously dropped into a reaction vessel. Alternatively, a solvent may be charged into a reaction vessel, and a mixture of the monomers and the solvent and a polymerization initiator solution may be continuously dropped into the reaction vessel, or a part or all of the monomers may be charged into the reaction vessel, and the polymerization initiator may be continuously dropped into the reaction vessel.

[0065] The polymerization initiator that can be used for copolymerization is not particularly limited, but when copolymerization is performed in an aqueous solvent, examples of the polymerization initiator include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate; and water-soluble organic peroxides such as t-butyl hydroperoxide. In this case, accelerators such as sodium hydrogen sulfite and Mohr's salt may be used in combination. In addition, when copolymerization is performed in a solvent such as a lower alcohol, an aromatic hydrocarbon, an alicyclic or aliphatic hydrocarbon, an ester, or a ketone, for example, peroxides such as benzoyl peroxide and lauryl peroxide; hydroperoxides such as cumene peroxide; and aromatic azo compounds such as azobisisobutyronitrile can be used as polymerization initiators. In this case, accelerators such as amine compounds may be used in combination. Furthermore, when copolymerization is performed in a water-lower alcohol mixed solvent, for example, the polymerization initiators or combinations of the polymerization initiator and accelerator described above can be appropriately selected and used. The polymerization temperature varies depending on the polymerization conditions such as the solvent used and the type of polymerization initiator, but is usually performed in the range of 50 to 120°C.

[0066] In the copolymerization, a chain transfer agent may be used to adjust the molecular weight, if necessary. Examples of the chain transfer agent used include known thiol compounds such as mercaptoethanol, thioglycerol, thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, octyl thioglycolate, and 2-mercaptoethanesulfonic acid; phosphorous acid, hypophosphorous acid, and salts thereof (sodium hypophosphite, potassium hypophosphite, etc.), sulfurous acid, hydrogen sulfite, dithionous acid, metabisulfite, and salts thereof (sodium sulfite, potassium sulfite, sodium hydrogen sulfite, potassium hydrogen sulfite, sodium dithionite, potassium dithionite, sodium metabisulfite, potassium metabisulfite, etc.), lower oxides and salts thereof; and the like. These may be used alone or in combination of two or more. Furthermore, in order to adjust the molecular weight of the copolymer, another monomer having higher chain transferability may be used as a monomer for obtaining the copolymer, in addition to the above-mentioned monomers. Examples of monomers with high chain transferability include (meth)allylsulfonic acid (salt) monomers. The content of such monomers in the copolymer is usually 20% by mass or less, and preferably 10% by mass or less.

[0067] When copolymerization is performed in an aqueous solvent to obtain a copolymer, the pH during polymerization is usually strongly acidic due to the influence of the monomer having an unsaturated bond, but this may be adjusted to an appropriate pH. If pH adjustment is required during polymerization, the pH can be adjusted using an acidic substance such as phosphoric acid, sulfuric acid, nitric acid, alkyl phosphoric acid, alkyl sulfuric acid, alkyl sulfonic acid, or (alkyl)benzenesulfonic acid. Among these acidic substances, phosphoric acid is preferably used because of its pH buffering effect. However, in order to eliminate the instability of the ester bond of the ester monomer, it is preferable to perform polymerization at a pH of 2 to 7. There is no particular limitation on the alkaline substance that can be used to adjust the pH, but alkaline substances such as sodium hydroxide and calcium hydroxide are common. The pH adjustment may be performed on a solution containing the monomer before polymerization, or on a solution containing the copolymer after polymerization. In addition, a part of the alkaline substance may be added before polymerization to perform polymerization, and then the pH of the solution containing the copolymer may be further adjusted.

[0068] [Asphalt emulsion composition for paving] The asphalt emulsion composition for paving of the present embodiment (hereinafter also simply referred to as the asphalt emulsion composition) contains the above-mentioned copolymer, and an asphalt emulsion containing asphalt, an emulsifier, and water, and the asphalt emulsion is at least one type of asphalt emulsion selected from the group consisting of cationic, anionic, and nonionic asphalt emulsions. The asphalt emulsion composition for paving of the present embodiment contains the above-mentioned copolymer, and therefore can form an asphalt coating that has excellent storage stability at high temperatures and reduced stickiness.

[0069] (copolymer) The copolymer used in this embodiment is the one described in the section [Tire adhesion suppressant]. The content of the copolymer is preferably 0.2 to 25 parts by mass, more preferably 1 to 20 parts by mass, even more preferably 3 to 20 parts by mass, even more preferably 5 to 18 parts by mass, and even more preferably 8 to 18 parts by mass, relative to 100 parts by mass of the asphalt emulsion. When the content of the copolymer is 0.2 parts by mass or more, an asphalt coating film with reduced stickiness can be obtained, and when it is 25 parts by mass or less, aggregation of the copolymer can be suppressed, and the storage stability of the asphalt emulsion composition at high temperatures can be improved.

[0070] (Asphalt emulsion) The asphalt emulsion used in this embodiment contains asphalt, an emulsifier, and water. The asphalt emulsion is at least one type of asphalt emulsion selected from the group consisting of cationic, anionic, and nonionic asphalt emulsions, and from the viewpoint of further exerting the effects of the present invention, a cationic asphalt emulsion is preferred. Note that the asphalt emulsion is classified into cationic, anionic, or nonionic asphalt emulsions depending on the type of emulsifier. The asphalt emulsion is not particularly limited, but examples thereof include "PK-1", "PK-2", "PK-3", "PK-4", "MK-1", "MK-2", and "MK-3" as specified in the Japanese Industrial Standard JIS K 2208 (2000); and "PK-P", "PK-H", "MK-C", "PKR-T", "PKR-S-1", and "PKR-S-2" as specified in the Japan Asphalt Emulsion Association Standard JEAAS-2006.

[0071] From the viewpoint of the standards for asphalt emulsions, the solid content of the asphalt emulsion is preferably 40 to 65 mass %, more preferably 40 to 62 mass %, and even more preferably 45 to 62 mass %.

[0072] The asphalt contained in the asphalt emulsion is not particularly limited, but examples thereof include natural asphalt such as lake asphalt, rock asphalt, and asphaltite, petroleum asphalt such as straight asphalt and blown asphalt, semi-blown asphalt, and hard asphalt. In addition, modified asphalt obtained by modifying these asphalts by blending thermosetting resins, thermoplastic resins, rubber, and the like may be used.

[0073] The content of asphalt is preferably from 25 to 65 mass %, more preferably from 30 to 65 mass %, and even more preferably from 30 to 60 mass %, based on the total mass of the asphalt emulsion.

[0074] The emulsifier contained in the asphalt emulsion may be any of cationic, anionic and nonionic emulsifiers. Among them, cationic emulsifiers are preferred from the viewpoint of exerting the effects of the present invention. Examples of the cationic emulsifier include primary amines, secondary amines, tertiary amines, quaternary ammonium salts, polyamines, and mixed amines thereof. Examples of the anionic emulsifier include fatty acid salts, alkyl sulfate salts, alkyl benzene sulfonates, alkyl naphthalene sulfonates, and rosinate salts. Examples of nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyethylene glycol fatty acid esters, and polyoxyethylene alkylamines.

[0075] The content of the emulsifier is preferably 0.1 to 10.0% by mass, more preferably 0.1 to 8.0% by mass, and even more preferably 0.1 to 5.0% by mass, relative to the total mass of the asphalt emulsion. When the content of the emulsifier is within the above range, aggregation of the asphalt emulsion can be suppressed, and the asphalt emulsion composition has better storage stability at high temperatures, as well as better mechanical stability and freezing stability.

[0076] The asphalt emulsion composition of the present embodiment may contain other additives as necessary in addition to the above-mentioned components. Examples of other additives include anti-aggregation agents such as salts of tertiary amines or polyamines neutralized with acids, quaternary ammonium salts, and the like; organic solvents such as aliphatic hydrocarbons and aromatic hydrocarbons; fluidizing agents; plasticizers, electrolytes such as calcium chloride, and adhesion inhibitors such as colloidal silica. Each of these additives may be used alone or in combination of two or more. In addition, the salts obtained by neutralizing tertiary amines or polyamines with acids and the quaternary ammonium salts exemplified as anti-agglomeration agents can also function as cationic emulsifiers, but when added to an asphalt emulsion composition containing an asphalt emulsion after emulsification, they are treated as anti-agglomeration agents.

[0077] The total content of other additives is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 0.1 to 100 parts by mass, more preferably 0.1 to 80 parts by mass, and even more preferably 0.2 to 50 parts by mass, relative to 100 parts by mass of the asphalt emulsion.

[0078] The asphalt emulsion composition of this embodiment has a storage stability measured in accordance with the JIS K 2208 (2000) "Storage Stability" test method of preferably less than 1.0 mass%, more preferably 0.8 mass% or less, and even more preferably 0.5 mass% or less. Specifically, the storage stability can be measured by the method described in the Examples.

[0079] [Method of manufacturing asphalt emulsion composition for paving] The method for producing an asphalt emulsion composition for paving according to the present embodiment includes the following step (i) or step (ii). Step (i): A step of mixing the copolymer with an emulsion containing the emulsifier and the water, and adding the asphalt to the resulting mixture to emulsify it. Step (ii): A step of emulsifying the asphalt with an emulsion containing the emulsifier and the water, and mixing the copolymer into the resulting asphalt emulsion.

[0080] [Step (i)] In this step, first, a copolymer is mixed with an emulsion containing an emulsifier and water to obtain a mixed liquid. The copolymer used is the one described in the section [Tire adhesion suppressant]. The emulsifier used is the one described in the section [Paving asphalt emulsion composition]. The emulsion is prepared by dissolving the emulsifier in water, which is preferably heated.

[0081] When producing a cationic asphalt emulsion composition, it is preferable to add an acid to the emulsion to adjust the pH at 40° C. to 1 to 6. Examples of the acid include hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, acetic acid, and glycolic acid, with hydrochloric acid and phosphoric acid being preferred.

[0082] The mixing is carried out using a stirrer, for example, a high-speed stirring and mixing device such as a disperser or homomixer, a media-type dispersing machine such as a paint shaker or a bead mill, or a mixing and stirring device such as an anchor blade.

[0083] The mixing is preferably carried out at a temperature of 40 to 80° C. for 0.1 to 3 hours, and more preferably at a temperature of 50 to 75° C. for 0.1 to 1 hour.

[0084] The content of the copolymer is preferably 0.5 to 10.0 mass% based on the mass of the emulsion, more preferably 1.0 to 8.5 mass%, and even more preferably 1.0 to 5.0 mass%. By adjusting the mixing ratio of the mixed liquid and the asphalt, the content of the copolymer per 100 parts by mass of the asphalt emulsion can be set within the above range.

[0085] Next, asphalt is added to the resulting mixture and emulsified using an emulsifier to obtain an asphalt emulsion composition. The asphalt may be that described in the section entitled “Asphalt Emulsion Composition for Paving.” Examples of the emulsifier include a colloid mill, a homogenizer, and a line mixer. The asphalt is emulsified by heating it to a molten state. The heating temperature is preferably 130 to 180°C, and more preferably 140 to 160°C.

[0086] [Step (ii)] In this process, first, asphalt is emulsified with an emulsion containing an emulsifier and water to obtain an asphalt emulsion. The asphalt and emulsifier used are those explained in the section [Asphalt emulsion composition for paving]. When a cationic emulsion is used as the emulsifier, it is preferable to add an acid to the emulsion to adjust the pH at 40° C. to 1 to 6. The acid used is the same as that described in the section [Step (i)]. The emulsification is carried out using an emulsifier. The emulsifier is the one described in the section [Step (i)]. The emulsification is carried out by heating the asphalt to a molten state. The heating temperature is preferably 130 to 180°C, more preferably 140 to 160°C.

[0087] The solid content of the resulting asphalt emulsion is preferably 40 to 65 mass %, more preferably 40 to 62 mass %, and even more preferably 45 to 62 mass %, from the viewpoint of the standards for asphalt emulsions.

[0088] The content of asphalt is preferably from 25 to 65 mass %, more preferably from 30 to 65 mass %, and even more preferably from 30 to 60 mass %, based on the total mass of the asphalt emulsion.

[0089] The content of the emulsifier is preferably 0.1 to 10.0% by mass, more preferably 0.1 to 8.0% by mass, and even more preferably 0.1 to 5.0% by mass, relative to the total mass of the asphalt emulsion. When the content of the emulsifier is within the above range, aggregation of the asphalt emulsion can be suppressed, and the asphalt emulsion composition has better storage stability at high temperatures, as well as better mechanical stability and freezing stability.

[0090] Next, the resulting asphalt emulsion is mixed with a copolymer to obtain an asphalt emulsion composition. As the copolymer, the one explained in the section [Tire adhesion suppressant] is used. The mixing is carried out using a stirrer or emulsifier. The stirrer and emulsifier used may be the same as those described in the section [Step (i)].

[0091] The content of the copolymer is preferably 0.2 to 25 parts by mass, more preferably 1 to 20 parts by mass, even more preferably 3 to 20 parts by mass, even more preferably 5 to 18 parts by mass, and even more preferably 8 to 18 parts by mass, relative to 100 parts by mass of the asphalt emulsion. When the content of the copolymer is 0.2 parts by mass or more, an asphalt coating film with reduced stickiness can be obtained, and when it is 25 parts by mass or less, aggregation of the copolymer can be suppressed, and the storage stability of the asphalt emulsion composition at high temperatures can be improved.

[0092] The method for producing an asphalt emulsion composition for paving of the present embodiment preferably includes the above-mentioned step (ii) in order to further exert the effects of the present invention.

[0093] The asphalt emulsion composition thus obtained is excellent in storage stability at high temperatures and can form an asphalt coating with reduced stickiness, and therefore can be suitably used as a prime coat for road paving, for curing concrete pavements such as cement-stabilized roadbeds, for tack coats, etc. It can also be suitably used as a spray material for surface treatment methods such as fog seal, chip seal, and slurry seal.

[0094] [Pavement] The pavement of this embodiment has one or more base layers and a surface layer, in that order, on a roadbed, and has an asphalt emulsion layer at least between the roadbed and base layer and between the base layer and the surface layer, and the asphalt emulsion layer is formed using the above-mentioned paving asphalt emulsion composition. The asphalt emulsion layer is formed using the asphalt emulsion composition for paving described above, and therefore has reduced stickiness. Therefore, when constructing a pavement, even if a construction machine runs on the asphalt emulsion layer, asphalt is less likely to adhere to the tires of the construction machine.

[0095] FIG. 1 is a schematic diagram showing one embodiment of a cross section of a pavement according to the present embodiment. The pavement 10 has a base layer 2 provided on a roadbed 1, and a surface layer 3 provided on the base layer 2. An asphalt emulsion layer 4 formed from the above-mentioned paving asphalt emulsion composition is provided at least between the roadbed 1 and base layer 2 and between the base layer 2 and surface layer 3. The asphalt emulsion layer 4 formed between the roadbed 1 and base layer 2 is also called a prime coat 4a, and the asphalt emulsion layer 4 formed between the base layer 2 and surface layer 3 is also called a tack coat 4b.

[0096] The roadbed 1 is composed of an upper roadbed and a lower roadbed, the lower roadbed is formed on the roadbed using crushed stone, and the upper roadbed is formed on the lower roadbed using crushed stone with adjusted grain size. Generally, crushed stone with a grain size of about 25 mm is used for the upper roadbed. The base layer 2 is a layer that has the role of evenly transmitting the load from the surface layer 3 to the roadbed 1, and is formed, for example, from a dense-grained asphalt mixture, a fine-grained asphalt mixture, a porous asphalt mixture, a modified asphalt mixture, or a gusset asphalt mixture. The surface layer 3 is a layer exposed on the surface of the pavement and is formed, for example, from an open-graded asphalt mixture or a dense-graded asphalt mixture.

[0097] The asphalt emulsion layer 4 is formed by spraying or applying the above-mentioned paving asphalt emulsion composition on the upper surface of the roadbed 1 or the upper surface of the base layer 2. The method of spraying or applying is not particularly limited, and any known method can be used. For example, spraying using a sprayer such as a distributor (vehicle for spraying asphalt emulsion) or an engine sprayer, or application using a roller brush, rubber rake, etc. can be mentioned.

[0098] The amount of the asphalt emulsion composition to be sprayed or applied is not particularly limited. In the case of a tack coat, the amount is, for example, 0.3 to 0.6 L / m, although it depends on the asphalt concentration in the asphalt emulsion composition. 2 In the case of a prime coat, for example, 1.0 to 2.0 L / m 2 It is preferable that the amount is about 100%.

[0099] After spraying or coating, it is preferable to cure the composition by a conventional method. The curing time is not particularly limited, but is usually about 30 minutes to several hours.

[0100] The asphalt emulsion composition is sprayed or applied and cured to form an asphalt emulsion layer 4 containing asphalt as a main component. The thickness of the asphalt emulsion layer 4 is not particularly limited and may be appropriately determined in consideration of the performance, but is usually within the range of 0.1 to 10 mm. The asphalt emulsion layer 4 is preferably a tack coat or prime coat, and is particularly preferably a prime coat. EXAMPLES

[0101] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited thereto. In the examples and comparative examples, "parts" means parts by mass unless otherwise specified.

[0102] (Production Example 1: Production of Copolymer (A-1)) In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device and a dropping device, 90 parts of water and 22 parts of (poly)ethylene glycol monoallyl ether (average number of moles of ethylene oxide added: 10) as a monomer represented by general formula (1) were added, and the temperature was raised to 100°C while stirring. Then, an aqueous monomer solution containing 11 parts of methacrylic acid as a monomer represented by general formula (3), 66 parts of methoxypolyethylene glycol methacrylate (average number of moles of ethylene oxide added: 25) as a monomer represented by general formula (2), 108 parts of 2-hydroxypropyl acrylate as a hydroxyalkyl (meth)acrylate, and 51 parts of water was added dropwise continuously for 2 hours to a reaction vessel maintained at 100°C. After the dropping was completed, the mixture was reacted for another hour while maintaining the temperature at 100°C to obtain a copolymer (A-1). The pH of this liquid was adjusted to 4 with a 30% by mass aqueous solution of sodium hydroxide to obtain an aqueous solution of copolymer (A-1). The copolymer (A-1) in the liquid had Mw=21,000 and Mw / Mn=2.6.

[0103] (Production Example 2: Production of Copolymer (A-2)) In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device and a dropping device, 90 parts of water and 22 parts of (poly)ethylene glycol monoallyl ether (average number of moles of ethylene oxide added: 10) as a monomer represented by the general formula (1) were added, and the temperature was raised to 100°C while stirring. Then, an aqueous monomer solution containing 12 parts of methacrylic acid as a monomer represented by the general formula (3), 66 parts of methoxypolyethylene glycol methacrylate (average number of moles of ethylene oxide added: 25) as a monomer represented by the general formula (2), 96 parts of 2-hydroxyethyl acrylate as a hydroxyalkyl (meth)acrylate, and 84 parts of water was added dropwise continuously for 2 hours to a reaction vessel maintained at 100°C. After the dropping was completed, the mixture was reacted for another hour while maintaining the temperature at 100°C to obtain a copolymer (A-2). The pH of this liquid was adjusted to 4 with a 30% by mass aqueous solution of sodium hydroxide to obtain an aqueous solution of copolymer (A-2). The copolymer (A-2) in the liquid had Mw=30,200 and Mw / Mn=2.7.

[0104] (Production Example 3: Production of Copolymer (a-1)) 164 parts of water was added to a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device, and a dropping device, and the temperature was raised to 100°C while stirring. Then, a monomer aqueous solution containing 169 parts of 2-hydroxypropyl acrylate as a hydroxyalkyl (meth)acrylate and 112 parts of water, and a mixed solution of 1 part of ammonium persulfate and 41 parts of water were continuously dropped into the reaction vessel maintained at 100°C for 2 hours each. After the dropping was completed, the mixture was further reacted for 1 hour while maintaining the temperature at 100°C to obtain copolymer (a-1). The copolymer (a-1) in the liquid had Mw=11,300 and Mw / Mn=2.9.

[0105] (Production Example 4: Production of Copolymer (a-2)) In a glass reaction vessel equipped with a thermometer, a stirrer, a reflux device and a dropping device, 190 parts of water and 50 parts of (poly)ethylene glycol monoallyl ether (average number of moles of ethylene oxide added: 35) as a monomer represented by the general formula (1) were added, and the temperature was raised to 100°C while stirring. Then, a monomer aqueous solution containing 117 parts of 2-hydroxypropyl acrylate as a hydroxyalkyl (meth)acrylate and 78 parts of water, and a mixed solution of 1 part of sodium persulfate and 44 parts of water were continuously dropped into the reaction vessel kept at 100°C for 30 minutes each. After the dropping was completed, the mixture was reacted for another hour while keeping the temperature at 100°C to obtain copolymer (a-2). The copolymer (a-2) in the liquid had Mw=40,100 and Mw / Mn=4.2.

[0106] The copolymers (A-1), (A-2), (a-1) and (a-2) thus obtained were subjected to the following evaluations, and the results are shown in Table 1.

[0107] [Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of copolymer] The Mw and Mw / Mn of the copolymer were determined in terms of standard polyethylene glycol by gel permeation chromatography (GPC) using the following measuring device and conditions: Measuring device: Tosoh Corporation Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard substance: Polyethylene glycol (Tosoh Corporation, GL Science Co., Ltd.) Detector: Differential refractometer (manufactured by Tosoh Corporation) Calibration curve; polyethylene glycol standard

[0108] [Table 1]

[0109] (Comparative Example 1: Production of Asphalt Emulsion Composition (1) (Asphalt Emulsion-1)) 0.4 parts by mass of mixed amine (mixture of primary amine, secondary amine, and tertiary amine) was added to 60 parts by mass of hot water at 70°C, and 0.4 parts by mass of acetic acid was added to prepare an amine salt. Then, 0.4 parts by mass of calcium chloride, an electrolyte, was added to produce an emulsion. 38.8 parts by mass of water was added to this emulsion, and the temperature of the emulsion was lowered to about 50°C. Then, 50 parts by mass of the emulsion and 50 parts by mass of asphalt modified with a thermoplastic resin at about 150°C were emulsified using a homogenizer (model number: Asahi Homogenizer LL type (research type), manufactured by SC Techno Co., Ltd.) to produce cationic asphalt emulsion-1 with an asphalt content of 50% by mass.

[0110] (Example 1: Production of asphalt emulsion composition (2)) 0.4 parts by mass of mixed amine (mixture of primary amine, secondary amine, and tertiary amine) was added to 60 parts by mass of hot water at 70 ° C., and 0.4 parts by mass of acetic acid was added to prepare an amine salt. Then, 0.4 parts by mass of calcium chloride, an electrolyte, was added to produce an emulsion. 1 part by mass of the copolymer (A-1) obtained in Production Example 1 was added to 61.2 parts by mass of this emulsion, and mixed using a homodisper (model number: DH-2.5, manufactured by Primix Corporation). 37.8 parts by mass of water was added to the resulting mixture, and the temperature of the emulsion was lowered to about 50 ° C., and then 50 parts by mass of the mixture and 50 parts by mass of asphalt modified with a thermoplastic resin at about 150 ° C. were emulsified using a homogenizer (model number: Asahi Homogenizer LL type (research type), manufactured by SC Techno Co., Ltd.) to obtain an asphalt emulsion composition (2) with an asphalt content of 50% by mass.

[0111] (Example 2: Production of asphalt emulsion composition (3)) An asphalt emulsion composition (3) having an asphalt content of 50 mass % was obtained in the same manner as in Example 1, except that the content of copolymer (A-1) was changed to 3 parts by mass.

[0112] (Example 3: Production of asphalt emulsion composition (4)) An asphalt emulsion composition (4) having an asphalt content of 50 mass % was obtained in the same manner as in Example 1, except that the content of copolymer (A-1) was changed to 5 parts by mass.

[0113] (Example 4: Production of asphalt emulsion composition (5)) 0.4 parts by mass of mixed amine (mixture of primary amine, secondary amine, and tertiary amine) was added to 60 parts by mass of hot water at 70°C, and 0.4 parts by mass of acetic acid was added to prepare an amine salt. Then, 0.4 parts by mass of calcium chloride, an electrolyte, was added to produce an emulsion. 38.8 parts by mass of water was added to this emulsion, and the temperature of the emulsion was lowered to about 50°C. Then, 50 parts by mass of the emulsion and 50 parts by mass of asphalt modified with a thermoplastic resin at about 150°C were emulsified using a homogenizer (model number: Asahi Homogenizer LL type (research type), manufactured by SC Techno Co., Ltd.) to produce cationic asphalt emulsion-1 with an asphalt content of 50% by mass. The copolymer (A-1) obtained in Production Example 1 was added to 100 parts by mass of the obtained cationic asphalt emulsion-1 so that the amount was 3 parts by mass, and mixed using a Homodisper (model number: DH-2.5, manufactured by Primix Corporation) to obtain an asphalt emulsion composition (5) having an asphalt content of 49% by mass.

[0114] (Example 5: Production of asphalt emulsion composition (6)) An asphalt emulsion composition (6) having an asphalt content of 48% by mass was obtained in the same manner as in Example 4, except that the content of copolymer (A-1) was changed to 5 parts by mass per 100 parts by mass of cationic asphalt emulsion-1.

[0115] (Example 6: Production of asphalt emulsion composition (7)) Cationic asphalt emulsion-1 Asphalt emulsion composition (7) having an asphalt content of 45% by mass was obtained in the same manner as in Example 4, except that the content of copolymer (A-1) was changed to 10 parts by mass per 100 parts by mass of the cationic asphalt emulsion-1.

[0116] (Example 7: Production of asphalt emulsion composition (8)) An asphalt emulsion composition (8) having an asphalt content of 42% by mass was obtained in the same manner as in Example 4, except that the content of copolymer (A-1) was changed to 18 parts by mass per 100 parts by mass of cationic asphalt emulsion-1.

[0117] (Example 8: Production of asphalt emulsion composition (9)) 0.4 parts by mass of mixed amine (mixture of primary amine, secondary amine, and tertiary amine) was added to 60 parts by mass of hot water at 70°C, and 0.4 parts by mass of acetic acid was added to prepare an amine salt. Then, 0.4 parts by mass of calcium chloride, an electrolyte, was added to produce an emulsion. 38.8 parts by mass of water was added to this emulsion, and the temperature of the emulsion was lowered to about 50°C. Then, 50 parts by mass of the emulsion and 50 parts by mass of asphalt modified with a thermoplastic resin at about 150°C were emulsified using a homogenizer (model number: Asahi Homogenizer LL type (research type), manufactured by SC Techno Co., Ltd.) to produce cationic asphalt emulsion-1 with an asphalt content of 50% by mass. To 100 parts by mass of the obtained cationic asphalt emulsion-1, 5 parts by mass of a salt obtained by neutralizing a tertiary amine with hydrochloric acid was added as an anti-aggregation agent, and mixed using a Homodisper (model number: DH-2.5, manufactured by Primix Corporation). Further, 20 parts by mass of the copolymer (A-1) obtained in Production Example 1 was added and mixed to 100 parts by mass of the above asphalt emulsion-1, thereby obtaining an asphalt emulsion composition (9) with an asphalt content of 40% by mass.

[0118] (Example 9: Production of asphalt emulsion composition (10)) An asphalt emulsion composition (10) having an asphalt content of 45 mass % was obtained in the same manner as in Example 6, except that the copolymer (A-1) was changed to the copolymer (A-2) obtained in Production Example 2.

[0119] (Comparative Example 2: Asphalt Emulsion Composition (11) (PK-3)) As the asphalt emulsion composition, "PK-3" specified in the Japanese Industrial Standard JIS K 2208 (2000) was used.

[0120] (Example 10: Production of asphalt emulsion composition (12)) 0.4 parts by mass of mixed amine (mixture of primary amine, secondary amine, and tertiary amine) was added to 60 parts by mass of hot water at 70 ° C., and 0.4 parts by mass of acetic acid was added to prepare an amine salt. Then, 0.4 parts by mass of calcium chloride, an electrolyte, was added to produce an emulsion. 3 parts by mass of the copolymer (A-1) obtained in Production Example 1 was added to 61.2 parts by mass of this emulsion, and mixed using a homodisper (model number: DH-2.5, manufactured by Primix Corporation). 35.8 parts by mass of water was added to the resulting mixture, and the temperature of the emulsion was lowered to about 50 ° C., and then 50 parts by mass of the emulsion and 50 parts by mass of straight asphalt at about 150 ° C. were emulsified using a homogenizer (model number: Asahi Homogenizer LL type (research type), manufactured by SC Techno Co., Ltd.), to obtain an asphalt emulsion composition (12) with an asphalt content of 50% by mass.

[0121] (Example 11: Production of asphalt emulsion composition (13)) As an asphalt emulsion, 10 parts by mass of the copolymer (A-1) obtained in Production Example 1 was added to 100 parts by mass of "PK-3" and mixed using a Homodisper (model number: DH-2.5, manufactured by Primix Corporation) to obtain an asphalt emulsion composition (13) with an asphalt content of 45% by mass.

[0122] (Comparative Example 3: Production of Asphalt Emulsion Composition (14) (Asphalt Emulsion-2)) 0.4 parts by mass of mixed amine (mixture of primary amine, secondary amine, and tertiary amine) was added to 60 parts by mass of hot water at 70°C, and 0.4 parts by mass of acetic acid was added to prepare an amine salt. Then, 0.4 parts by mass of calcium chloride, an electrolyte, was added to produce an emulsion. 38.8 parts by mass of water was added to this emulsion, and the temperature of the emulsion was lowered to about 50°C. Then, using a homogenizer (model number: Asahi Homogenizer LL type (research type), manufactured by SC Techno Co., Ltd.), 40 parts by mass of the emulsion and 60 parts by mass of asphalt modified with thermoplastic resin and wax at about 150°C were emulsified to produce cationic asphalt emulsion-2 with an asphalt content of 60% by mass.

[0123] (Example 12: Production of asphalt emulsion composition (15)) An asphalt emulsion composition (15) having an asphalt content of 55 mass % was obtained in the same manner as in Example 6, except that cationic asphalt emulsion-2 was used as the asphalt emulsion.

[0124] (Example 13: Production of asphalt emulsion composition (16)) An asphalt emulsion composition (16) having an asphalt content of 48 mass % was obtained in the same manner as in Example 8, except that cationic asphalt emulsion-2 was used as the asphalt emulsion.

[0125] (Comparative Example 4: Production of Asphalt Emulsion Composition (17)) Cationic Asphalt Emulsion-2 as Asphalt Emulsion 20 parts by mass of colloidal silica (BESIL (registered trademark)-30S, manufactured by A-GREEN CO., LTD.) to which 3 parts by mass of hydrochloric acid had been added was added to 100 parts by mass of the asphalt emulsion, and mixed using a Homo Disper (model number: DH-2.5, manufactured by Primix Corporation) to obtain an asphalt emulsion composition (17) with an asphalt content of 50% by mass.

[0126] (Comparative Example 5: Production of Asphalt Emulsion Composition (18)) An asphalt emulsion composition (18) having an asphalt content of 45 mass% was obtained in the same manner as in Example 6, except that the copolymer (A-1) was changed to the copolymer (a-1) obtained in Production Example 3.

[0127] (Comparative Example 6: Production of Asphalt Emulsion Composition (19)) An asphalt emulsion composition (19) having an asphalt content of 45 mass% was obtained in the same manner as in Example 6, except that the copolymer (A-1) was changed to the copolymer (a-2) obtained in Production Example 4.

[0128] The following evaluations were carried out on the asphalt emulsion compositions obtained in Examples 1 to 13 and Comparative Examples 1 to 6. The results are shown in Table 2.

[0129] [Tire adhesion rate (40℃, 50℃, 60℃)] In accordance with the Japan Asphalt Emulsion Association Standard (JEAAS) (2020), the adhesion rate to the rubber sheet was measured at 40°C, 50°C, and 60°C using a wheel tracking tester (model number: AI-1100-3ST, manufactured by Iwata Kogyosho Co., Ltd.). A slate board measuring 300 mm long x 300 mm wide and 3 mm thick (classified as a soft board according to JIS A 5430 (2013) fiber-reinforced cement board) was coated with an asphalt emulsion composition at a solid content of 300 g / m 2 The asphalt emulsion composition was left to cure at room temperature (20° C.) until it was completely decomposed, and a test specimen was prepared. The material of the rubber sheet was natural rubber, and the rubber hardness was JIS hardness 84±4 at 20°C and 78±2 at 60°C. The rubber sheet was 1 mm thick and molded into a strip (length 300±10 mm, width 60±3 mm). The tire adhesion rate was measured by a wheel tracking test according to the following procedures (1) to (7). (1) The prepared specimen and the molded rubber sheet are cured for at least four hours in a thermostatic chamber adjusted to the specified temperature (40±1°C, 50±1°C, or 60±1°C). (2) Measure the mass of the rubber sheet immediately before the test. (3) Place the rubber sheet on the part of the test specimen where the tire runs, and move the tire back and forth once with a load of 624±10N. (4) After the tire has been driven, the rubber sheet is peeled off vertically with a constant force within 2 seconds. (5) The mass of the rubber sheet is quickly measured to determine the mass of the adhered asphalt coating. (6) The above steps (1) to (5) shall be carried out at least three locations per test specimen. (7) Tire adhesion rate is calculated using the following formula. In addition, the values ​​of Examples 2 to 9 and Comparative Examples 5 to 6 in Table 2 are relative values ​​when the value of Comparative Example 1 is set to 100, the values ​​of Examples 10 to 11 are relative values ​​when the value of Comparative Example 2 is set to 100, and the values ​​of Examples 12 to 13 and Comparative Example 4 are relative values ​​when the value of Comparative Example 3 is set to 100. Tire adhesion rate (mass%) = [Rubber sheet mass after test (g) - Rubber sheet mass before test (g)] / [Tire running area (m 2 ) × Asphalt emulsion composition solid content application amount (g / m 2 )] x 100

[0130] [Table 2]

[0131] The asphalt emulsion compositions of Examples 1 to 13, which contained the tire adhesion inhibitor of this embodiment (a copolymer having a specific structure), all reduced the tire adhesion rate of the resulting asphalt coating, and the effect of reducing stickiness was confirmed.

[0132] (Examples 14 to 20 and Comparative Examples 7 to 12) The asphalt emulsion compositions (1), (5) to (11), (14), (15) and (17) to (19) obtained above were evaluated as follows. The results are shown in Table 3.

[0133] [Storage stability (20℃, 60℃)] The storage stability of the asphalt emulsion compositions was measured after standing for 24 hours at room temperature (20°C) in accordance with the JIS K 2208 (2000) "storage stability" test method. In addition, the storage stability of the asphalt emulsion compositions (15) and (17) was measured after standing for 24 hours at a temperature of 60°C. The lower the value, the less separation of the asphalt emulsion composition, and there is no problem in practical use if the value is less than 1% by mass.

[0134] [Table 3]

[0135] It can be seen that all of the asphalt emulsion compositions of Examples 14 to 20, which contain the tire adhesion inhibitor of this embodiment (copolymer containing a specific structure), have excellent storage stability. The asphalt emulsion composition of Comparative Example 10, which contains silica, has a storage stability of 1.0% by mass or more after standing at 60°C for 24 hours, indicating poor storage stability at high temperatures. In contrast, the asphalt emulsion composition of Example 20 has a storage stability of 0.5% by mass after standing at 60°C for 24 hours, indicating excellent storage stability at high temperatures.

[0136] (Example 21 and Comparative Example 13) The asphalt emulsion compositions (11) and (13) obtained above were used to carry out the following evaluations. The results are shown in Table 4.

[0137] [Shear strength test (23℃, -10℃)] A specified amount of dense-grained asphalt mixture containing aggregate with a maximum particle size of 13 mm and polymer-modified asphalt type II was spread evenly into a formwork measuring 300 mm in length and 300 mm in width, and then compacted with a roller to the specified density to form the base layer (asphalt mixture layer). The asphalt emulsion composition was applied to the surface of the base layer using a sprayer at a rate of 0.6 L / m 2 and then cured at room temperature (20°C) for 24 hours to form an asphalt emulsion layer. A specified amount of dense-graded asphalt mixture containing aggregate with a maximum particle size of 13 mm and polymer-modified asphalt type II was spread evenly on the asphalt emulsion layer and compacted to a specified density with a roller to form a base layer (asphalt mixture layer), and a test specimen (pavement) consisting of base layer 1 / asphalt emulsion layer / base layer 2 was prepared. The base layer 1 of the specimen removed from the formwork was fixed to a load measuring device (model number: AG-100kNX, manufactured by Shimadzu Corporation) set to the measurement temperature, and a shear force (loading rate: 1 mm / min) was applied to base layer 2 (the unfixed base layer) in a direction parallel to the surface on which the asphalt emulsion layer was formed, and the shear strength (MPa) and the displacement (mm) at maximum strength were measured. An asphalt emulsion layer can be said to have excellent adhesion if it has a shear strength of 0.15 MPa or more and a displacement of 1 mm or more at maximum strength at 23°C. Also, an asphalt emulsion layer can be said to have excellent adhesion if it has a shear strength of 0.8 MPa or more and a displacement of 0.5 mm or more at maximum strength at -10°C.

[0138] [Table 4]

[0139] The pavement of Example 21 has high shear strength at 23°C and -10°C, and also has a large displacement at maximum strength at both temperatures, indicating that it has excellent adhesion. [Explanation of symbols]

[0140] 10 Pavement 1 Roadbed 2 Base layer 3 Surface layer 4 Asphalt emulsion layer 4a Prime Coat 4b Tuck coat

Claims

1. A tire adhesion inhibitor characterized by containing a copolymer including a structural unit (a) derived from a monomer represented by the following general formula (1), a structural unit (b) derived from a monomer represented by the following general formula (2), and a structural unit (c) derived from a hydroxyalkyl (meth)acrylate: 【Chemistry 1】 [In the formula, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O's, they may be the same or different. n1 is the average number of moles of oxyalkylene groups added, and represents a number from 1 to 100. 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. 【Chemistry 2】 [In the formula, R 3 , R 4 and R 5 Each of A and B independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. m represents a number from 0 to 2. 2 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O's, they may be the same or different. n2 is the average number of moles of oxyalkylene groups added and is a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.]

2. The tire adhesion inhibitor according to claim 1, wherein the copolymer has a content of the structural unit (a) of 5 to 30 mass%, a content of the structural unit (b) of 15 to 60 mass%, and a content of the structural unit (c) of 30 to 80 mass%.

3. The tire adhesion inhibitor according to claim 1 or 2, wherein the hydroxyalkyl (meth)acrylate is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate.

4. 3. The tire adhesion inhibitor according to claim 1, wherein the copolymer has a weight average molecular weight (Mw) of 5,000 to 100,000.

5. The present invention comprises a copolymer including a structural unit (a) derived from a monomer represented by the following general formula (1), a structural unit (b) derived from a monomer represented by the following general formula (2), and a structural unit (c) derived from a hydroxyalkyl (meth)acrylate, and an asphalt emulsion including asphalt, an emulsifier, and water, The asphalt emulsion composition for paving, wherein the asphalt emulsion is at least one type of asphalt emulsion selected from the group consisting of cationic, anionic and nonionic asphalt emulsions. 【Chemistry 3】 [In the formula, R 1 represents an alkenyl group having 2 to 5 carbon atoms; A 1 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O's, they may be the same or different. n1 is the average number of moles of oxyalkylene groups added, and represents a number from 1 to 100. 2 represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms. 【Chemistry 4】 [In the formula, R 3 , R 4 and R 5 Each of A and B independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. m represents a number from 0 to 2. 2 O represents an oxyalkylene group having 2 to 18 carbon atoms, and when there are a plurality of O's, they may be the same or different. n2 is the average number of moles of oxyalkylene groups added and is a number from 1 to 100. X represents a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms.]

6. 6. The asphalt emulsion composition for paving according to claim 5, wherein the content of said copolymer is 0.2 to 25 parts by mass per 100 parts by mass of said asphalt emulsion.

7. 7. The asphalt paving emulsion composition according to claim 5, wherein the hydroxyalkyl (meth)acrylate is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate.

8. A method for producing the asphalt emulsion composition for paving according to claim 5 or 6, A method for producing an asphalt emulsion composition for paving, comprising the following step (i) or step (ii): Step (i): A step of mixing the copolymer with an emulsion containing the emulsifier and the water, and adding the asphalt to the resulting mixture to emulsify it. Step (ii): A step of emulsifying the asphalt with an emulsion containing the emulsifier and the water, and mixing the copolymer into the resulting asphalt emulsion.

9. The method for producing an asphalt emulsion composition for paving according to claim 8, comprising the step (ii).

10. A pavement having one or more base layers and a surface layer in this order on a roadbed, and an asphalt emulsion layer at least between the roadbed and the base layer and between the base layer and the surface layer, A pavement, wherein the asphalt emulsion layer is formed using the asphalt emulsion composition for paving according to claim 5 or 6.

Citation Information

Patent Citations

  • Asphalt emulsifier

    JP2001323165A

  • Asphalt emulsion composition and its production method

    JP2004091761A

  • Emulsifier composition for asphalt and asphalt emulsion using the composition

    JP2005320449A

  • Additive for a hydraulic composition

    JP2014125397A

  • Copolymer and use thereof

    JP2014218619A